What is the crucial difference between the metabolic consequences of cadmium and zinc treatment of the plants? - Hegedűs, Attila (Acta Biologica Szegediensis, 2005)
Heavy metal stress induced alterations in the activities of several representatives of the enzymatic antioxidant defense system such as guaiacol peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX) were comparatively studied in barley seedlings and alfalfa aldose reductase overexpressing transgenic tobacco treated by Zn and/or Cd. Although roots were the main sites of metal accumulation, metals induced oxidative damage mainly in the leaves. Our experiments clearly show that the investigated heavy metals have quite different effects on plant metabolism and induce the protective enzymatic system in different ways. Transgenic tobacco plants showed increased tolerance against cadmium induced stress.